Local Culture Synchronization in Global Contemporary Fashion Style Breakthroughs - Tiko Prabhata; Ilham Ari Susanto; Savira P.; Wegig Murwonugroho (Mudra Jurnal Seni Budaya, 2023)
Fashion now has become an inherent part of people’s lives, especially in urban settings. One’s fashion sense may be expressed in numerous ways, such as by donning unique clothing, wearing accessories that carry certain identities, or putting on symbols with special meanings or messages. Over the past few years, contemporary fashion design has returned to traditional design values in ethnic motifs, shapes, and even technologies used. Such a phenomenon is worth close observation, drawing interest in how traditional art creative concepts are processed into part of contemporary-styled fashion. To answer this question, this research employed the phenomenological method. From the analysis carried out, the following four appealing traditional values in contemporary design works were identified: 1) symbolization; 2) environmentally friendly materials; 3) traditional technologies; and 4) philosophies. These four values are the most frequently adapted by designers in creating contemporary fashion designs. Finally, we theorize about the ability of symbolic representations of a particular culture to be transferred to fashion over time, without losing the bond with the local tradition.